Michel Serres, Topology and Folded Time in Christopher Nolan's Dunkirk. Issue 3 (September 2022) - Hunt, Kevin
Abstract : This article discusses Michel Serres's topological thinking and his approach to space and time from a film studies perspective, specifically looking at connections between Serresian philosophy and the work of Christopher Nolan, using Dunkirk (2017) as an example of folded time. The article provides a selective overview of Serres's topological thinking, which opposes a geometrical approach to space and time, as well as indicating connections between Serresian thought and film studies more broadly. Serres makes frequent use of visual metaphors that rely upon motion, which means discussing Serres's philosophy in relation to film can be a purposeful way to make sense of his topological thinking about spatialized time. Serresian philosophy can bring new ideas to film studies while discussion of Serres's thinking from a film studies perspective can help to visualize some of his philosophical ideas. The article considers similarities with, and distinctions from, Gilles Deleuze's understanding of time in cinema, which is modelled on the work of Henri Bergson. One essential difference is that Serres approaches topological time in relation to space whereas Deleuze only considers topological aspects to time through the virtual qualities of the non-spatialized time-image. Key aims of the article are to contribute to film studies through the application of Serresian thinking in relation to Dunkirk as well as offering a new approach to the recurrent themes of space and time in Nolan's work. The main objective is to present Serresian topological thinking as an alternative approach to space and time in film studies, which includes the capability to potentially complement or enhance ideas developed by Deleuze and Bergson. In keeping with Serresian philosophy this article pursues a new way of thinking about folded time in relation to film, based upon exploring new territory and synthesizing ideas rather than attempting to present a universal argument.